A Review of Sustainable and Renewable Sources of Energy for Afghanistan - Qasimi, Abdul Baser; Isazade, Vahid; Toomanian, Ara (Journal of Renewable Energy and Mechanics, 2022)
Supplying energy demands in Afghanistan is a serious problem, providing demanded energy for consumption is mostly provided by neighboring countries, especially Iran, Turkmenistan, Uzbekistan, and Tajikistan. Domestic production of energy covers only an only small portion of energy demands in the country. In this regard, the energy supply in this country is extremely vulnerable and indicates non-sustainability. This study was intended to review available conducted research and published articles and reports. the results obtained from these reviews show that the utilization of renewable energy, especially, solar and wind energy, resources in Afghanistan is the only reliable and sustainable solution for the energy problem in this country. The results of the review of the previous research indicate that Afghanistan has great potential for renewable energy sources. the country has sources of renewable energy, including solar, wind, and geothermal energy.